2021
DOI: 10.3390/w13233406
|View full text |Cite
|
Sign up to set email alerts
|

Policy, Technology, and Management Options for Water Conservation in the Ogallala Aquifer in Kansas, USA

Abstract: The Ogallala Aquifer underlies 45 million ha, providing water for approximately 1.9 million people and supporting the robust agriculture economy of the US Great Plains region. The Ogallala Aquifer has experienced severe depletion, particularly in the Southern Plains states. This paper presents policy innovations that promote adoption of irrigation technology, and management innovations. Innovation in Kansas water policy has had the dual effects of increasing the authority of the state to regulate water while a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…A meta‐analysis on the irrigation systems between 1990 and 2016 in the Texas High Plains indicated that furrow, center pivot, and subsurface drip irrigation systems increased water use efficiency by 14%, 99%, and 147%, respectively, relative to drylands (Mitchell‐McCallister et al, 2020). In addition, many other innovations in irrigation technology and management have been applied to the agriculture in the region in the past two decades, including scheduling irrigation, planting drought tolerant crop varieties, and deficit irrigation applications with monitoring ET, soil moisture, and plant stress (Evett et al, 2020; Rudnick et al, 2019; Smidt et al, 2016; Sophocleous, 2010; Steiner et al, 2021; Stove & Buchanan, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta‐analysis on the irrigation systems between 1990 and 2016 in the Texas High Plains indicated that furrow, center pivot, and subsurface drip irrigation systems increased water use efficiency by 14%, 99%, and 147%, respectively, relative to drylands (Mitchell‐McCallister et al, 2020). In addition, many other innovations in irrigation technology and management have been applied to the agriculture in the region in the past two decades, including scheduling irrigation, planting drought tolerant crop varieties, and deficit irrigation applications with monitoring ET, soil moisture, and plant stress (Evett et al, 2020; Rudnick et al, 2019; Smidt et al, 2016; Sophocleous, 2010; Steiner et al, 2021; Stove & Buchanan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The eight states of the High Plains take different approaches to the development and management of the water resources based on each state's water laws that abide by different legal doctrines, thus causing substantial differences in regional water management efforts (Ifft et al, 2018; Sophocleous, 2010; Steiner et al, 2021). The intensive irrigation development in Nebraska led lawmakers to put regulations in place to prevent the over‐appropriation of both surface and groundwater since 1972.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the SD-6 LEMA exceeded the original conservation goals and reduced irrigationwater withdrawals by 26-31% (Deines, Kendall, Butler, et al, 2019;Drysdale & Hendricks, 2018) and slowed water table decline rates (Butler et al, 2020;Whittemore et al, 2023) with only minor negative impacts on yield and none on profitability (Golden, 2018). As such, the SD-6 LEMA is a successful example of irrigator-driven groundwater conservation (Marston, Zipper, et al, 2022) and has motivated the development of additional conservation approaches around the state (Steiner et al, 2021).…”
Section: Sheridan-6 Local Enhanced Management Areamentioning
confidence: 99%
“…Ensuring sustainability across spatial scales is necessary to avoid disproportionate impacts outside of the local watershed. In some regions, water systems may require time to recover, particularly in those regions with significant groundwater depletion (Basso et al 2013, Steiner et al 2021 or legacy pollution (Basu et al 2022). A balance will have to be struck, as current users should not be unduly penalized for past actions.…”
Section: Defining Sustainable Agricultural Water Limitsmentioning
confidence: 99%